An easily controllable flash sintering process for densification of electrolyte for application in solid oxide fuel cells. (10th July 2020) - Zhang, Jing; Zhao, Yating; Qiao, Jinshuo; Sun, Wang; Sun, Kening; Wang, Zhenhua
Abstract: A step-wise current-limiting flash sintering process (SCFS process) was proposed to densify La0.8 Sr0.2 Ga0.8 Mg0.2 O3-δ (LSGM) electrolyte. Well-densified microstructures of LSGM samples were obtained at 690 °C under an electric field of 100 V cm −1 . Compared with the current-limiting flash sintering process, the spike in power dissipation was avoided, the shrinkage rate of LSGM samples was moderate, and the microstructures of LSGM samples were uniform. The conductivity of LSGM samples sintered via SCFS process at 0.9 A for 30 min reached 0.072 S cm −1 at 850 °C, and this was approximately the same as the value of conventionally sintered LSGM samples at 1400 °C for 10 h. These results proved that SCFS process achieved easy controllability, and it is expected that SCFS process can be applied in industry. Highlights: SCFS process was proposed for LSGM electrolyte densification. The well-densified and uniform microstructures of LSGM were obtained. The spike in power dissipation was avoided in SCFS process. SCFS process is expected to be applied in industry.